2017
DOI: 10.1136/bmjgast-2017-000132
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the wireless motility capsule and lactulose breath testing in the evaluation of patients with Parkinson's disease who present with functional gastrointestinal symptoms

Abstract: BackgroundThe aetiology and origin of gastrointestinal symptoms in Parkinson's disease (PD) remains poorly understood. Gastroparesis, small bowel transit delay and bacterial overgrowth may, individually or collectively, play a role.AimsIn patients with PD and functional gastrointestinal symptoms, we aimed to determine the utility of the wireless motility capsule and lactulose breath tests in further defining their symptoms' aetiology.MethodsIn this retrospective cohort study, consecutive patients with PD and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Small intestinal transit has been investigated using different ambulatory systems comprised of an ingestible capsule and a wireless data receiver [ 102 , 103 , 104 ]. These studies reported a delay in small intestinal transit time in PD compared to matched controls, although the magnitude of delayed transit was less marked than that seen in the colon.…”
Section: Objective Measures Of Gastrointestinal Dysfunctionmentioning
confidence: 99%
“…Small intestinal transit has been investigated using different ambulatory systems comprised of an ingestible capsule and a wireless data receiver [ 102 , 103 , 104 ]. These studies reported a delay in small intestinal transit time in PD compared to matched controls, although the magnitude of delayed transit was less marked than that seen in the colon.…”
Section: Objective Measures Of Gastrointestinal Dysfunctionmentioning
confidence: 99%
“…Of all the extracted articles, 245 articles were excluded because they were duplicates, reviews, or irrelevant studies. Finally, 11 studies [ 7 , 10 19 ] (7 cross-sectional studies and 4 cohort studies) with 973 participants (692 PD patients and 281 controls) met the inclusion criteria (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…New work suggests a strong association between PD and SIBO. The prevalence of SIBO in PD reported in recent research was 34% [ 7 ]. However, current studies do not provide explicit evidence to confirm the correlation at home and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…However, in people with types 1 and 2 diabetes, rates of gastroparesis overall are estimated to be approximately 5% and 1%, respectively, and are reported to be 40% and 10-20%, respectively, at tertiary care medical centers, where reported rates are likely to be elevated [33,48]. Formal prevalence studies of gastroparesis have not been performed in patients with PD, but reports involving small patient samples have provided frequency estimates from 35 to 100% [25,49,50]. Prevalence estimates have varied according to the criteria used in studies, because not all patients with DGE experience GI symptoms [25].…”
Section: Gastroparesismentioning
confidence: 99%